PENGARUH MENTORING DOSEN PEMBIMBING AKADEMIK TERHADAP PRESTASI AKADEMIK MAHASISWA - Fransisca Desiana Pranatasari (Business Management Journal, 2016)
The main tasks of lecturers in education is mentoring. Topics mentoring can be anything, including the related to their academic achievement. This research is the development of previously conducted research using a qualitative approach to sample 5 student informants. The study resulted in the finding that the lecturer's role as a mentor is needed in the educational environment entepreneurship. The aim of this study was conducted to see mentoring influence lecturer with student achievement increased done with quantitative approach. Data was collected using purposive sampling. The criteria used is minimal student academic mentoring activities three times in the first half had been a student with a minimum of 1 year and students are students majoring in Management University Ciputra. The result mentoring has a positive influence on students' academic achievement as students are encouraged to get the best value according to their targets.Keywords: mentoring, student academic achievement, entrepreneurship, education environment